Efek Beta Karoten dan Agregasi Klorofil Pada Fotostabilitas Klorofil a dalam Pelarut Aseton - Costa, Junet. F. da; Karwur, Ferry F; Limantara, Leenawaty (Jurnal Natur Indonesia, 2009)
Chlorophyll as photosynthetic pigment has many benefits to human such as antioxidant, antibacterial, color additive,immunity, and photosensitizer. Concerning to these applications, chlorophyll a will react with oxygen and light andreduce its effectiveness. It is then important to understand the stability of chlorophyll a on oxygen and light.Stability of chlorophyll a in the presence of beta-carotene (1:1) in acetone was studied for various waterconcentrations. Each solution was exposed to red light (ë e” 630 nm) for 0.5; 1.0; 2.5; 5.0; 10; 20; 30; 40; 50; and 60minutes and their spectrum were analysed. When water was added (8.33; 16.67; 25; 33.33; 41.67; 50; 58.33; 66.67;75; and 83.33 percent) to the acetone solution of chlorophyll a, the chlorophylls aggregate, and in the presence ofbeta-carotene, the chlorophyll more stable. The water shifts the chlorophyll a spectrum toward red duringillumination with or without the presence of carotene. The formation of oligomeric chlorophyll a aggregate occurswithin 10-20 minutes after the water was applied. This strategy of aggregating the chlorophylls to dissipateexcess energy captured from light does not support the photostability of chlorophyll as much as beta-carotene.Surprisingly, when beta carotene was mixed with 66.7% and 75.0% of water, the chlorophyll a degraded 5.56% and9.71% respectively. In conclusion, the aggregate form of chlorophyll a and the presence of beta-carotene increasephotostability of chlorophyll a in acetone solution.